Digital social work practice through social networking sites. Case study with users of Social Services Community Centre from Malaga (Spain) on Facebook - Castillo de Mesa, Joaquin; López Peláez, Antonio; Méndez Domínguez, Paula (Groupwork, 2021)
Isolation is a clear indicator of social exclusion. To tackle it, we wondered if it would be possible to improve digital skills and strengthen bonds through online groups on a social networking site. This paper presents the results of an experimental study carried out in Malaga (Spain) with unemployed users of social care services. From the perspective of social work practice with groups, this study aims at strengthening bonds and mutual help through improving digital skills. This was carried out using a Facebook group as a shared space for community empowerment. To know the impact of these interactions, netnography and social network analysis were conveyed, as well as algorithms to identify communities and assess cohesion. Results showed that Facebook groups may be effective tools to promote active learning and mutual support and which can be used effectively by social workers.